2015
DOI: 10.1097/mol.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of flavin monooxygenase 3 in cholesterol metabolism and atherosclerosis

Abstract: Purpose of Review Atherosclerosis and associated cardiovascular disease (CVD) still remain the largest cause of mortality worldwide. Several recent studies have discovered that metabolism of common nutrients by gut microbes can produce a proatherogenic metabolite called trimethylamine-N-oxide (TMAO). The goal of this review is to discuss emerging evidence that the hepatic enzyme that generates TMAO, flavin monooxygenase 3 (FMO3), plays a regulatory role in maintaining whole body cholesterol balance and atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…The most obvious phenotypic difference in rare individuals who are homozygous for loss of function of FMO3 alleles is a distinct fishy body odor smell known as trimethylaminuria; named for the malodourous compound, trimethylamine (TMA), that FMO3 normally quickly metabolizes (8). It is now known that the formation of TMA and oxidation product trimethylamine-N-oxide (TMAO) is reliant on gut microbiota-dependent metabolism of dietary precursors such as choline and carnitine (9, 10). Previously, it was believed that the FMO3 product TMAO was a benign compound, but emerging data now implicate TMAO’s importance as a biomarker or possibly causative contributor to coronary artery disease, diabetes, and kidney disease risk (7, 1013).…”
Section: Emerging Roles Of Fmo3 In Cardio-metabolic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious phenotypic difference in rare individuals who are homozygous for loss of function of FMO3 alleles is a distinct fishy body odor smell known as trimethylaminuria; named for the malodourous compound, trimethylamine (TMA), that FMO3 normally quickly metabolizes (8). It is now known that the formation of TMA and oxidation product trimethylamine-N-oxide (TMAO) is reliant on gut microbiota-dependent metabolism of dietary precursors such as choline and carnitine (9, 10). Previously, it was believed that the FMO3 product TMAO was a benign compound, but emerging data now implicate TMAO’s importance as a biomarker or possibly causative contributor to coronary artery disease, diabetes, and kidney disease risk (7, 1013).…”
Section: Emerging Roles Of Fmo3 In Cardio-metabolic Diseasementioning
confidence: 99%
“…Using genetically modified mouse models or anti-sense oligo nucleotide silencing (ASO), at least three independent laboratories have now shown that FMO3 plays important roles in reverse cholesterol transport, glucose and insulin signaling, lipid metabolism, and metabolic dysfunction (7, 9, 20, 21). Shih et al, showed that a decrease in FMO3 lowered circulating TMAO as well as reduced plasma and liver levels of glucose and lipids in a mouse model highly susceptible to atherosclerosis (21).…”
Section: Emerging Roles Of Fmo3 In Cardio-metabolic Diseasementioning
confidence: 99%
“…This enzyme is microsomal, FAD-and NADPH-dependent and, is able to activate molecular oxygen to catalyse substrate oxygenation [1][2][3]4]. Recently, in addition to xenobiotic metabolism, FMO3 has also been implicated in the development of atherosclerosis, cholesterol imbalance and to glucose and lipid metabolism [5][6][7]. Human FMO3 activity is widely recognized as being part of the first-pass metabolism of drugs together with the superfamily of cytochrome P450 enzymes [1].…”
Section: Introductionmentioning
confidence: 99%
“…The natural polymorphism of FMO enzymes has been shown to strongly influence interindividual drug response increasing the significance of these enzymes from a pharmacological as well as toxicological point of view [7,8]. Human FMO3 is a highly polymorphic enzyme and many of its single nucleotide polymorphisms are present at reasonably high frequency within the population [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in addition to its role in drug metabolism, FMO3 has also been shown more recently to act as an important modifier of human health in atherosclerosis and cholesterol/glucose/lipid metabolism (Leiser et al, 2015;Schugar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%